PENGEMBANGAN STUDI ULUMUL QUR’AN - Muhamad Ali Mustofa Kamal (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2019)
This paper is a personal examination of the writer to try for offering the hermeneutical philosophy who initiated by Friedrich Schleiermacher as aids in interpreting the Holy Qur’an. Schleiermacher offers about the principles of hermeneutics as an exegesis tool that consists of grammatical interpretation and psychological interpretation. In the realm of ulumul Qur’an (Qur’anic sciences), Schleiermacher’s thought it could serve as a tool in a interpreter (mufassir) when interpreting the holy Qur’an, especially accompany the commentator to appropriate of pre-understanding. His open minded principles in the work of philosophical hermeneutics added perspective when analyzing the problem of the meaning of a text; can deliver the commentator to explore the grammatical and psychological aspect when the scope of the Qur’anic text is understood. The elements of ulumul Qur’an in order to understand the language of the Qur’an as a reflection on the problem of linguistic, stylistic issues, and problems exegetic, can be analyzed with a sharp understanding by model the framework of Schleiermacher hermeneutics that formulated the grammatical and psychological interpretation.